2011
DOI: 10.4049/jimmunol.1003166
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN Substitutes for T Cell Help during Viral Infections

Abstract: Certain virus infections depend on the presence of T cell help for the generation of primary CD8+ T cell responses. However, the mechanisms that render these particular viral infections T cell help dependent is largely unknown. In this study, we compared CD8+ T cell responses elicited by lymphocytic choriomeningitis virus infection, as prototype of a T cell help independent infection, with T cell help dependent CD8+ T cell responses induced by vaccinia virus infection. In this paper, we show that a key paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
63
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 53 publications
7
63
0
Order By: Relevance
“…Immune responses that do not elicit strong inflammatory cytokines require CD4 + T cell help for optimal generation of CTLs (37). Our study shows that DC-intrinsic LTbR signaling represents an important help signal that regulates the induction of IFN-I.…”
Section: Discussionmentioning
confidence: 84%
“…Immune responses that do not elicit strong inflammatory cytokines require CD4 + T cell help for optimal generation of CTLs (37). Our study shows that DC-intrinsic LTbR signaling represents an important help signal that regulates the induction of IFN-I.…”
Section: Discussionmentioning
confidence: 84%
“…In these settings, the lack of CD4 T cell help during priming results in defective memory CTLs that mediate effector functions but do not undergo a second round of clonal expansion on Ag rechallenge (7,11,12). However, several studies in mice have indicated that the requirement for CD4 T cell help is not absolute and can be bypassed by the intense inflammatory environment elicited by certain pathogens (13)(14)(15)(16)(17)(18) or several TLR ligands (13,(19)(20)(21).…”
mentioning
confidence: 99%
“…IFNs-I also promote CTL responses in an indirect manner by delivering maturation signals to DCs and by modulating the degree of Ag presentation and costimulation (5). Furthermore, T cell-intrinsic IFN-I signaling was reported to substitute for T cell help to CTLs (6). Although not considered specifically to be signal 3 cytokines, other cytokines, such as the common cytokine receptor g-chain family (7) and IFN-g (8), also have a profound effect on the CTL response.…”
mentioning
confidence: 99%